Perancangan Buku Interaktif Cerita Rakyat Lombok “Monyeh” - Mirnayati Mirnayati; I Nyoman Yoga Sumadewa (Universitas Bumigora, 2020)
Folklore is an oral cultural heritage that needs to be preserved because folklore is part of the cultural wealth of Nusantara. However, the lack of publications makes many folk tales still unknown to the public, especially children. One of the folk tales that are less well known to the public is the folklore from Lombok entitled monyeh. So it is necessary to have a publication media to introduce this folklore, one of which is through interactive books that can attract children to read, so they do not get bored while reading and are more informative.This interactive book of monyeh folk tales is designed using the design thinking method to get the right problem-solving solution in designing. There are two media in the design, namely the primary media of interactive folklore books, monyeh and secondary media, namely x-banners and merchandise. By designing this interactive book, it is hoped that it can become a new media choice to introduce the Lombok Monyeh folklore.